2020
DOI: 10.3390/nano10122409
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Synthesis of Molybdenum Oxide and Its Silica Nanoparticle Composites for Dye Degradation

Abstract: The molybdenum oxide (MoO3) and MoO3@SiO2 nanoparticles were successfully prepared using the chemical bath deposition (CBD) method. The photocatalytic activities of molybdenum oxide (MoO3), SiO2, and MoO3@SiO2 nanoparticles composite have shown a synergistic photocatalytic effect of SiO2 combined with MoO3. The first-order degradation rate constants for MoO3, SiO2, and MoO3@SiO2 nanocomposite were 10.3 × 10−3 min−1, 15.1 × 10−3 min−1, and 16.3 × 10−3 min−1, respectively. The MoO3@SiO2 composite showed degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The MoONPs exhibit a uniform hexagonal rod‐like morphology. The regular faceted surface of each hexagonal rod is clearly visible, as depicted in Figure 6 (Kamoun et al, 2020). EDS shows the elemental composition of MoONPs as shown in Figure 7.…”
Section: Resultsmentioning
confidence: 96%
“…The MoONPs exhibit a uniform hexagonal rod‐like morphology. The regular faceted surface of each hexagonal rod is clearly visible, as depicted in Figure 6 (Kamoun et al, 2020). EDS shows the elemental composition of MoONPs as shown in Figure 7.…”
Section: Resultsmentioning
confidence: 96%
“…From the obtained data, it can be concluded that the SiO2 NPs prepared from rice husk ash can be used as a powerful photodegradation catalyst for toxic dyes. The experimental data of kinetic behavior for photocatalytic degradation of MO using SiO2 NP photocatalyst were fitted by the first-order relation as follows [68]:…”
Section: Photodegradation Performancementioning
confidence: 99%
“…This is explained by the charge transfer from a bonding orbital of Si-O to a 2p nonbonded orbital of nonbridging oxygen [24]. According to the literature, oxygen defects or metal/metal The experimental data of kinetic behavior for photocatalytic degradation of MO using SiO 2 NP photocatalyst were fitted by the first-order relation as follows [68]:…”
Section: Probable Mechanism For Photocatalytic Degradation Of Mo Dyementioning
confidence: 99%
“…In general, it appears in three different structures such as orthorhombic (α), monoclinic (β), and hexagonal crystallographic phases. The α phase is the most stable state among them, where the phase stability and crystal structure are dictated by the MoO 6 octahedra, which are made up of six 'O' atoms and one 'Mo' atom [5][6][7][8][9]. From an application perspective, it has a variety of domains ranging from optoelectronic devices, chromism, energy storage, and catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…MoO 3 thin films can be prepared using a variety of processes, which includes CVD, MOCVD, PVD, sol-gel, hydrothermal, atomic layer deposition, molecular-beam epitaxy (MBE), and spray pyrolysis [6][7][8][9][10][11][12][13]. Among these techniques, spray pyrolysis thin-film coating is a facile and low-cost approach to fabricate large-area thin-film structures.…”
Section: Introductionmentioning
confidence: 99%